2020
DOI: 10.21608/jram.2020.24735.1042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of microRNA 126 in diabetic retinopathy in type 2 diabetes mellitus

Abstract: Background: Diabetes mellitus (DM) is a group of metabolic disorders characterized by chronic hyperglycemia. It is caused by defective insulin production or resistance of the cells to insulin. The chronic hyperglycemia leads to damage of different organs, especially eyes, kidneys, nerves, heart, and blood vessels. MicroRNAs (miRNAs) are small noncoding regulatory ribonucleic acids (RNA). Many studies have showed the association between miRNA 126 and complications of DM including diabetic retinopathy (DR). Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The sample size for two study groups in the present study was calculated depending on the previous study conducted by Kamel et al, 2020 55 for miR-126 and using the statistical software G* power (3.1.9.2). The ΔCT values (mean ± SD) for miR-126 in the plasma of DNR and NPDR subjects were used for effect size (d) calculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size for two study groups in the present study was calculated depending on the previous study conducted by Kamel et al, 2020 55 for miR-126 and using the statistical software G* power (3.1.9.2). The ΔCT values (mean ± SD) for miR-126 in the plasma of DNR and NPDR subjects were used for effect size (d) calculation.…”
Section: Methodsmentioning
confidence: 99%
“… 53 Though retinal vascular endothelial dysfunction and angiogenesis are the pathological features of advanced stages of DR, 2 , 3 it remains unknown whether the expression of miR-132 alters in DR. Thus, in the present study, we used miR-126 that has been shown to be decreased in different tissues by different investigators, 54 , 55 targets VEGF 50 , 51 and a novel miR (miR-132) that also modulated by VEGF, a principal mediator for DR. 7 , 53 It is also to be noted that even several miRs were deregulated in DR, there are limited studies to demonstrate that levels of miRs in plasma could distinguish NPDR from DNR. 55 …”
Section: Introductionmentioning
confidence: 99%